The Implementation of Active Learning In Teaching Writing at The Eighth Grade of SMP Negeri 5 Boyolali In 2013 / 2014 Academic Year - Nurjannah, Lia Wahyu (JoLLIET, 2015)
This research aims at describing active learning in teaching writing at the eighth grade of SMP Negeri 5 Boyolali in 2013 / 2014 academic year. The objectives of this research are : (1) to describe the implementation of active learning in teaching writing at SMP Negeri 5 Boyolali consisting the goals of teaching writing, the techniques of active learning in teaching writing, the procedures of active learning in teaching writing, and the media used of active learning in teaching writing. (2) to describe the problems faced by the teacher in applying active learning. (3) to describe the problems faced by the students.The writer uses descriptive research. The subject of this research are the students and the English teacher of the eighth grade of SMP Negeri 5 Boyolali in 2013/2014 academic year. The writer gets the data of this research from event, informant, and document. The methods of collecting data are interview, observation, and analyzing document.The results of the analysis show that (1) the implementation of active learning in teaching writing at SMP Negeri 5 Boyolali, consists of the goals of teaching writing are as follows: the students are expected identify the genre of the text, the students are expected able to make one genre of the text, and the students are expected able to give answer based on the question from the text; the techniques of active learning in teaching writing are as follows: question and answer, scrambled sentence, and group discussion; the procedures of active learning in teaching writing are as follows: observing, questioning, collecting information, and communicating; and the media used of active learning in teaching writing are as follows: students materialâs book, laptop, projector, and LCD. (2) the problems faced by the teacher in applying active learning are as follows: managing the class, the lack of media, and there are still teachers who canât operate media of teaching learning. (3) the problems faced by the students are as follows: limited vocabulary, too many task and exercises in writing activities, and not all students liked active learning technique.